The effect of hip dysplasia on some biochemical parameters, oxidative stress factors and hematocrit levels in dogs - Polat, E.; Han, M. C.; Kaya, E.; Yilmaz, S.; Kayapinar, S. D.; Coskun, S.; Can, U. K. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2021)
In this study, it was aimed to investigate the effect of hip dysplasia on some biochemical parameters, oxidative stress factors and hematocrit values in dogs. Hematocrit values (HTC), (CK) activities and oxidative stress factors were evaluated in a total of 27 dogs with healthy hip joints (n: 11) and hip dysplasia (n: 16). There was no statistically significant difference between the two groups in terms of HCT, Ca and P values (p>0.05). ALP and CK activities were found to be statistically significantly increased in the group with hip dysplasia compared to the control group with a healthy hip joint (p<0.05). While malondialdehyde (MDA) level, one of the oxidative stress factors, was increased in the group with hip dysplasia, decreased glutathione (GSH) levels, catalase (CAT) and glutathione peroxidase (GSH-Px) activities were significantly decreased. There was no significant difference between the two groups in terms of superoxide dismutase (SOD) level. As a result, it was determined that oxidative stress factors differ in dogs with hip dysplasia compared to dogs with the healthy hip joint.
Keywords: alkaline phosphatase; hematocrit; hip dysplasia; creatine kinase; oxidative stress